Harp and Electronics: Composition, Design, and Performance. - Monaghan, Úna (Contemporary Music Review, 2019)
This article outlines methods, considerations, and challenges for composing and performing with harp and electronics, investigated over the last five years. My background is in Irish traditional music and in experimental, contemporary, and computer music, as a composer, programmer, performer, and sound engineer. The harp, as a resonant and multiphonic instrument, presents specific challenges for the design of interfaces for computer sound control. I explain in detail my motives, approach, and decision-making in developing new technologies and music for harp and electronics. In particular, I present conclusions drawn from working with Camac's MIDI harp, and I consider questions of rhythm and flexibility in electronics control that are particularly relevant to traditional dance musics. I conclude with my most recent work on the control of electronics via microphones and movement sensors to exploit an existing playing gesture. I highlight the importance of considering performance, composition, and technological questions in parallel.